Faecal microbiota transplantation as a novel approach for autism-associated anxiety: A critical therapeutic appraisal - Tanushree D. Malode; Pranali Chandurkar; Brijesh G. Taksande; Amol A. Tatode; Mohammad Qutub; Tanvi Premchandani; Milind J. Umekar; Jayshree B. Taksande (Medicine in Microecology)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by social communication deficits and restrictive, repetitive behaviors. A significant proportion of individuals with ASD also suffer from anxiety disorders, further compounding their behavioral and emotional challenges. Conventional therapies for anxiety in ASD, including pharmacological and behavioral interventions, often yield suboptimal results and carry notable limitations. Growing research highlights the critical role of the gut-brain axis in neurodevelopment and emotional regulation, with gut microbiota dysbiosis increasingly implicated in both ASD and anxiety pathogenesis. Faecal microbiota transplantation (FMT), a therapeutic approach aimed at restoring microbial homeostasis by transferring fecal material from healthy donors, has emerged as a novel intervention of interest. Preclinical studies have demonstrated that alterations in gut microbiota can modulate social behaviors and anxiety-like symptoms, with FMT reversing many pathological features in animal models. Early clinical investigations, though limited, suggest that FMT may improve gastrointestinal health, core ASD symptoms, and comorbid anxiety. Mechanistically, FMT is thought to reduce neuroinflammation, restore neurotransmitter balance, and normalize stress responses by enhancing gut microbial diversity and metabolic function. However, significant challenges remain, including concerns about safety, standardization, donor selection, and regulatory approval. Future research must focus on large-scale, controlled trials and the identification of biomarkers predictive of FMT response to establish its therapeutic potential more conclusively. This review critically examines the existing evidence, explores the mechanistic pathways linking gut microbiota to anxiety in ASD, and discusses the future directions necessary to translate FMT into a viable clinical strategy for autism-associated anxiety.